2013
DOI: 10.1021/cm303344z
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Monodisperse Maghemite and Ferrite Nanocrystals from Metal Powder and Octanoic Acid

Abstract: Extremely small, monodisperse, and spheric maghemite (γ-Fe2O3, 2–3 nm) and manganese (4–7 nm), cobalt (3–5 nm), and zinc ferrite (5–7 nm) nanocrystals are directly accessible on a large scale starting from inexpensive metal powders and octanoic acid by thermolysis in a high-boiling solvent. Bigger particle size is obtainable by prolonged reaction time according to the Ostwald ripening principle. The superparamagnetic nanocrystals and their assembly have been characterized by transmission electron microscopy, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…1a; δ = 0.37 mm/s, QS = 0.60 mm/s) are comparable to those observed for 11 nm nanostructured zinc ferrite prepared by high energy ball milling [6] and to 10 nm zinc ferrite NPs synthesized from ferric nitrate solution [7]. It can be concluded that the small particle sizes (3-7 nm, [3]) lead to a fast superparamagnetic relaxation resulting in doublets at room temperature. We attribute the observed deviations from lorentzian line shape to those particles, which do not relax faster than the Mössbauer time window of ∼10 −7 s. For MnFe 2 O 4 NPs a quadrupole splitting of 0.57 mm/s is observed (Fig.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…1a; δ = 0.37 mm/s, QS = 0.60 mm/s) are comparable to those observed for 11 nm nanostructured zinc ferrite prepared by high energy ball milling [6] and to 10 nm zinc ferrite NPs synthesized from ferric nitrate solution [7]. It can be concluded that the small particle sizes (3-7 nm, [3]) lead to a fast superparamagnetic relaxation resulting in doublets at room temperature. We attribute the observed deviations from lorentzian line shape to those particles, which do not relax faster than the Mössbauer time window of ∼10 −7 s. For MnFe 2 O 4 NPs a quadrupole splitting of 0.57 mm/s is observed (Fig.…”
Section: Resultssupporting
confidence: 73%
“…For the sample with the smallest particle size (CoFe 2 O 4 , 3-5 nm [3], see Fig. 3c,f) the relative area of the spin-canting component is higher than in the two other samples (50 %) whereas the calculated canting angle is 59 • .…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations